Maternal Plasma Elabela, a Biomarker for the Severity and Kidney Function of Human Preeclampsia - Miaoyan Ma; Yuemin Hou; Jinfang Wu; Yanhua Qi (Clinical and Experimental Obstetrics & Gynecology)
Background: It reported that serum Elabela level was decreased in preeclampsia patients. However, there is no researcher done the study on the correlations between plasma Elabela and kidney function, blood pressure, blood glucose and lipid in preeclampsia patients. Our objective is determined whether plasma Elabela could be a marker for the severity and kidney function of preeclampsia. Methods: 72 pregnant women were enrolled in this study and divided into healthy group (n = 37), mild preeclampsia group (n = 20) and severe preeclampsia group (n = 15). The level of plasma Elabela was detected using ELISA. Results: Plasma Elabela was reduced in preeclampsia patients compared to healthy group, and severe preeclampsia patients had the lower level of Elabela and poorer kidney function. The level of plasma Elabela was negatively correlated with those of uric acid (UA), creatinine (Cre), cystatin C (CysC), systolic blood pressure (SBP) and diastolic blood pressure (DBP). Conclusions: Lower concentration of plasma Elabela correlated with worse kidney function, and higher blood pressures in preeclampsia patients.